Photoinduced Elimination in 2,3-Dihydro-2-tert-butyl-3-benzyl-4(1H)-quinazolinone: Theoretical Calculations and Radical Trapping Using TEMPO Derivatives - Cabrera-Rivera, Fanny Araceli; Ortíz-Nava, Claudia; Escalante, Jaime; Hernández-Pérez, Julio M.; Hô, Minhhuy (Synlett, 2012)
Photochemical irradiation of 2,3-dihydro-2-tert-butyl-3-benzyl-4(1H)-quinazolinone produced 3-benzyl-4(3H)-quinazolinone through photoinduced elimination via a radical mechanism. The use of photochemical conditions such as chloroform and UV irradiation (λ = 254 nm) got the 3-benzyl-4(3H)-quinazolinone in a high yield. Some theoretical calculations were achieved to explain the mechanism and the presence of radical intermediates was confirmed by trapping with different 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) derivatives.
Keywords: 2,3-dihydro-4(1H)-quinazolinones; mechanism; photochemical reaction; 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO); AIM; MO analysis; density analysis